Tradisi Barzanji Syaban Masyarakat Bugis Wajo Tanjung Jabung Timur - Junaid, M. (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2005)
This study attempts to answer why Wajo Buginese practice reading barzanji Syaban, how it has been impIemented, and what values can be taken from it. Wajo Buginese believe that Syaban is the last month of the yea4 the time to poy the vow or the promise, and the time to convey gratitude to God (Allah). After doing all these, Waio Buginese will feel released, happy, and safe.